Biodegradation of Premium Motor Spirit using surfactant-expressing bacteria from mechanic workshops in Malumfashi, Katsina State, Nigeria - Aminu Aliyu; Benjamin Chikwendu Onusiriuka; Yahaya Abdullahi Umar; Kamaluddeen Kabir; Haroun A. A. (UMYU Journal of Microbiology Research)
Biosurfactant-expressing bacteria have been shown to have potential in many biotechnological applications including the biodegradation of petroleum fractions, such as premium motor spirit (PMS). This study was aimed at investigating the potential use of biosurfactant-expressing bacterial isolates in the biodegradation of premium motor spirit (PMS) at various concentrations (100-100,000ppm). The biosurfactant-expressing bacteria were isolated from mechanic workshop in Malumfashi, Katsina, Nigeria using standard techniques. The isolates identified belonged to the genera Acinetobacter, Bacillus, Micrococcus, Pseudomonas and Stenotrophomonas. These isolates were screened for biosurfactant expression using drop collapse, haemolysis, oil–water behavior assays and emulsification index test. Positives isolates were investigated for PMS degradation by growing the isolates on mineral salt media supplemented with (0.1ml) premium motor spirit (PMS) as sole source of carbon. Although, higher total hydrocarbon degrading bacterial counts were obtained from soils where isolates positive for biosurfactant expression are predominant, there was no statistically significant difference between isolate source using Kruskal-Wallis H test (p = 0.67). The isolates Bacillus velezensis and Stenotrophomonas maltophilia were positive for biosurfactant-production potential using drop-collapse, β-haemolysis, oil spreading, and emulsification index and drop collapse tests with higher tolerance to PMS at concentrations up to 100,000 ppm. Statistical analysis using multiple-comparison analysis of variance (ANOVA) confirmed that the isolates exhibited varying PMS degradation response (p = 0.0066); furthermore, the tolerance of the bacteria to the PMS is dose-dependent (p = 0.00012). Post-hoc analysis using Tukey’s test identified Bacillus velezensis as the most efficient biosurfactant-producing and hydrocarbon degrading isolate (p = 0.0264 and 0.0034); moreover, the threshold concentration for high PMS tolerance was found to be 1000ppm and above (p = 0.0174, 0.0008 and 0.0001).These isolates’ ability to grow on mineral salt media supplemented with PMS as a sole source of carbon presents a veritable avenue for exploitation in biotechnology, towards biosurfactants-mediated bioremediation of hydrocarbon pollutants in oil contaminated soils.